Efeito do haloperidol ou risperidona sobre parâmetros comportamentais, inflamatórios e dopaminérgicos em cérebro de ratos - Peroza, Luis Ricardo (2016)
Schizophrenia is a psychiatric disorder that affects about 1% population around the world and its pharmacological treatment consist in the use of antipsychotics. Haloperidol, a first generation antipsychotic (FGA) acts primarily by blocking dopamine D2 receptors, while risperidone, a second generation antipsychotic (SGA), also acts through antagonism of serotonin receptors 5-HT2A serotonin receptor. Among the side effects related to the use of these drugs are the motor disorders, which are more related to the use of SGA. Tardive dyskinesia (TD), a behavioral disorder associated with chronic antipsychotic treatment, is characterized by involuntary movements, predominantly on the orofacial region, and its pathophysiology is not well understood. This study aimed to evaluate behavioral, inflammatory and dopaminergic changes in rats treated with haloperidol (1.0 mg/kg/day) or risperidone (2 mg/kg/day) for 28 days. There was a significant increase on vacuous chewing movements (VCM) in rats treated with haloperidol, but not risperidone, as well as a decrease in locomotor and exploratory activity. Both antipsychotic increased the levels of pro-inflammatory cytokines (interleukin-1β [IL-1β], interleukin-6 [IL-6], tumor necrosis factor-α [TNF- α] and γ interferon [IFN-γ]) and decreased the anti-inflammatory (interleukin-10 [IL-10]) in the striatum. Correlation analysis showed a positive relation between increased number of VCM and IL-1β and INF-γ levels. Oxidative and antioxidant markers (levels of thiobarbituric acid reactive substances [TBARS], catalase and protein and nonprotein thiols) showed no significant changes in the cortex of rats treated with both antipsychotics. The activity of the enzyme monoamine oxidase (MAO-A and MAO-B) in the cerebral cortex, in rats treated with haloperidol or risperidone remained in the control group levels and the immunoreactivity of the enzyme tyrosine hydroxylase (TH) and dopamine transporter (DAT), showed no significant difference when evaluated also in the cortex of animals treated with both antipsychotics. Analyzing together, the results suggest that elevated levels of inflammatory markers can be linked to the development of DT. However, these results should be treated with reserve, once the risperidone-treated group also showed a change in cytokine levels. Also, suggest that treatment with haloperidol or risperidone does not change the parameters dopaminergic and does not cause oxidative damage in the cerebral cortex, suggesting that the cortex may not be related to the development of motor disorder.